Dinâmica do componente arbóreo em um remanescente de floresta estacional semidecidual em Araguari, Minas Gerais, Brasil - Pádua, Kim Junqueira Manna (2014)
CHAPTER I: Dynamics studies in tropical forests had been and continue to be fundamental to the characterization and understanding of plant communities and population s diversity and complexity over time. This study aimed to compare the phytosociological structure, floristic composition and community dynamics, making possible the identification of future trends in populations and consequently in community. The studied area called Água Fria, is located in Fazenda da Mata s protection área. In each plot were recorded, sampled and identified all living trees with BHC (breast height circumference) ≥ 15cm for the years 2007 and 2012 and this period dynamics calculated based on an exponential model. Regarding to phytosociology, species, individuals, families, basal area, diversity and evenness were practically constant. Trichilia catigua and T. clausseni recruited individuals and rose in VI, while Eugenia florida lost individuals, but it was not enough to lose position in the rank. The average mortality rate of the tree community was 2,4 % year and recruitment 2,61 % year. Overall, the results suggests a net increase in density (0,21 % year) and a net loss in the basal area (-1,12 % year). It was expected the otherwise, due to common process in preserved areas known as \"selfthinning\". This observation allows us to affirm that the area is going through a particular process, in which, despite being an area in advanced stage of succession, large individuals are still dying and density is increasing. This makes important future studies that assay the rainfall of the area and an evaluation of the site\'s location in a valley that may have been a defining factor for the mortality of large individuals. CHAPTER II: Tropical forests are characterized by their high plant diversity and complexity, resulting from the heterogeneity of vegetation in spatial and temporal scales. To reduce the variance of the data set, reveal differences between species and even functional ecosystem characteristics, a common practice used in vegetation analysis is to classify plants in response and functional groups. A comparison was made between the percentage of functional groups present in the study area, between two surveys (2007 and 2012) and, based on mortality rates and recruitment, we created groups of dynamic response to elucidate the behavior of the most important species (N ≥ 10). Among the functional groups, the results indicate that the community remained constant over the five years, which was expected for the fragment studied, since it is already in an advanced successional stage. Stands out for the response groups, three species. Eugenia florida, which showed high mortality and didn t recruit any individual, Trichilia clausseni and T. catigua, which recruited individuals and rose in VI. Although these species were located in different response groups, and present inverse dynamic behaviors, those didn t cause changes in the functional diversity of the species because they play the same role in the environment. However, the environmental conditions which these species are subject may influence this process of community building over time. Other factors, such as monitoring time, sampling and rainfall conditions in that period or prior periods may also influence in higher or lower dynamics rates. In relation to the hypothesis, the groups analysis allowed us to conclude that the area remains in a good conservation condition and it is important to study them, because they are more stable than the populations separately, and therefore, should be used in management and conservation plans.